2021
DOI: 10.4103/jmss.jmss_18_20
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Permanent Device for Fertility Period Detection by Basal Body Temperature and Analysis of the Cervical Mucus Potential of Hydrogen

Abstract: Background: Sometimes, women find it difficult to conceive a baby and others use contraceptives that often have side effects. Researchers have already established the importance of measuring basal body temperature (BBT) and the potential of hydrogen (pH). Method: We have designed and realized a device that allows the simultaneous measurement of the BBT and the pH. We used an Arduino Uno board, a pH sensor, and a temperature sensor. The device communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…More recently, new technology including wearable sensors has demonstrated that measuring multiple physiological parameters has the potential to utilize FABM methods more accurately than methods that utilize only postovulatory shifts in the BBT [2,5,12]. Most of the current fertility tracking devices or mobile phone applications combine mechanisms of calendar cycle tracking, cervical mucus interpretation, urinary LH testing and/or BBT [13][14][15]. As a consequence, they necessitate multiple active diagnostic measures by the user, which result in an effort that is comparable to the previously available FABM methods.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, new technology including wearable sensors has demonstrated that measuring multiple physiological parameters has the potential to utilize FABM methods more accurately than methods that utilize only postovulatory shifts in the BBT [2,5,12]. Most of the current fertility tracking devices or mobile phone applications combine mechanisms of calendar cycle tracking, cervical mucus interpretation, urinary LH testing and/or BBT [13][14][15]. As a consequence, they necessitate multiple active diagnostic measures by the user, which result in an effort that is comparable to the previously available FABM methods.…”
Section: Introductionmentioning
confidence: 99%